UJI SIFAT MEKANIKA KAYU JATI (Tectona grandis L.F) ASAL DESA PULU KECAMATAN DOLO SELATAN KABUPATEN SIGI SULAWESI TENGAH - Husain, Sadam; Hapid, Abdul; ., Mutmainnah (Jurnal Warta Rimba, 2019)
Teak (Tectona grandis L. F) is one of the forestry plants that has various advantages and is a tropical and subtropical plant known as trees that have high quality and are of high selling value because teak is included in strong class II, durable class I, and luxury class I. That is why teak is much needed in the property industry, furniture industry craftsmen, household handicrafts, light weight construction, this study aims to determine the mechanical properties that include firm fiber press firmness, static curvature (MOE) and broken firmness (MOR) from teak (Tectona grandis L. F) from Pulu Village, South Dolo District, Sigi Regency, Central Sulawesi. This study uses a Completely Randomized Design (CRD) with three position treatments in the stem, namely the base, middle and end. Each treatment was repeated six times so that there were 18 experimental sample units. Based on the results of the study it can be concluded that, statistically the position in the stem has no significant effect on the firmness of the press parallel to the teak wood, MOE and MOR originating from the village of Pulu, South Dolo Subdistrict, Sigi, Central Sulawesi. Firmness press parallel to the fiber at the base of 371.94 kg / cm2, middle 342.24 kg / cm2 and tip 326.25 kg / cm2. Static arch strength (MOE) at base 94,000.19 kg / cm², center 88,216.01 kg / cm2 and end section 89,196.19 kg / cm². Broken firmness (MOR) at the base portion of 914.80 kg / cm², center 861.15 kg / cm² and the lowest value at the end section 802.89 kg / cm².Keywords: Mechanics, Teak Wood, MOE, MOR, Firmness Press Parallel Fiber.